Dear Little One - Laden, Nina (Simon & Schuster Books for Young Readers, 2021)
"This lyrical picture book celebrates all the wonder and beauty in the natural world, featuring Mother Nature personified. From the treasure of flowers to the mystery of insects this book encourages children to explore their world and be grateful for all that surrounds them"--